Design and results of the Fifth Answer Set Programming Competition - Calimeri, Francesco; Gebser, Martin; Maratea, Marco; Ricca, Francesco (Artificial intelligence, 2016)
Answer Set Programming (ASP) is a well-established paradigm of declarative programming that has been developed in the field of logic programming and non-monotonic reasoning. Advances in ASP solving technology are customarily assessed in competition events, as it happens for other closely related problem solving areas such as Boolean Satisfiability, Satisfiability Modulo Theories, Quantified Boolean Formulas, Planning, etc. This paper reports about the fifth edition of the ASP Competition by covering all aspects of the event, ranging from the new design of the competition to an in-depth analysis of the results. The paper comprises also additional analyses that were conceived for measuring the progress of the state of the art, as well as for studying aspects orthogonal to solving technology, such as the effects of modeling. A detailed picture of the progress of the state of the art in ASP solving is drawn, and the ASP Competition is located in the spectrum of related events.